Premature ejaculation among men attending outpatient clinic in Universiti Sains Malaysia hospital and it’s associated factors - Mohd Roslan , Ahmad Zamree (2017)
Premature ejaculation (PE) is a common male sexual disorder.Several factors have been proven to be associated with PE namely erectile dysfunction, general medical condition and psychological illness. However, there is little data on prevalence of premature ejaculation according to its four subtypes;lifelong PE, acquired PE, natural variable PE and premature-like ejaculatory dysfunction.To determine the prevalence of premature ejaculation and its associated factors among men attending outpatient clinic in USM hospital.A cross sectional study among men aged 18 to 60 years old was conducted from January 2014 to January 2015. Premature Ejaculation Diagnostic Tool (PEDT) and 5-item International Index of Erectile Function (IIEF-5) questionnaire were distributed. Participants who were identified as having premature ejaculation were further assessed with 21-item Depression, Anxiety and Stress Scale. Premature ejaculation was defined as PEDT score of 9 and above. A total of 294 men recruited in this study with the mean (SD) age of 46.3 (10.1) years. The prevalence of PE was 21.4% (n=63). Among those with PE, 7.9% (n=5), 15.9% (n=10), 58.7% (n=37), 17.5% (n=11) were identified as lifelong PE, acquired PE, natural variable premature ejaculation and premature like ejaculatory dysfunction respectively. Multiple logistic regression showed that only mild erectile dysfunction (ED) [adj. OR (95% CI): 5.65 (1.89, 16.91)], p=0.002) mild-moderate ED [adj. OR (95% CI): 8.2 (2.72, 24.46), p:<0.001] and moderate-severe ED [adj. OR (95% CI): 6.0 (1.15, 31.23), p=0.03] were significantly associated with premature ejaculation. The proportion of depression, anxiety and stress among men with PE in this study were 20.6%, 33.3% and 14.3% respectively. More than two third of them discussed their ejaculatory problem with others. The prevalence of premature ejaculation in this study was comparable with other regions. Erectile dysfunction was the only factor that significantly associated with PE but no association were seen between age, ethnicity, educational and occupational status, frequency of sexual intercourse, smoking status or underlying comorbidities. Men who were detected as having PE in this study also reported certain degree of anxiety, depression and stress.